Serum Analysis in Patients with Temporomandibular Disorders: A Controlled Cross-Sectional Study in Norway - Kordian Staniszewski; Henning Lygre; Trond Berge; Annika Rosén (Pain Research and Management)
Temporomandibular disorder (TMD) is characterized by pain and dysfunction in the temporomandibular join (TMJ) and the masticatory apparatus. Associations with autoimmune diseases, inflammatory conditions, and nutrition deficiencies have been reported in previous studies of TMD patients. To evaluate essential proteins, hormones, electrolytes, and vitamins in serum from TMD patients, a standard blood sample analysis was performed in 60 TMD patients and 60 healthy controls matched for age and gender, retrieving 19 different analyses. We found that TMD patients had significantly higher values of hemoglobin (p=0.036), cobalamin (p=0.023), albumin (p=0.005), parathyroid hormone (PTH) (p=0.038), and vitamin D (p=0.005), and significantly lower values of creatinine (p=0.006) and potassium (p=0.011), compared to controls. In the TMD group, most of the determinants had a wider range, and several subjects, compared to the control group, had values outside the normal reference area. However, most of the TMD patients and controls had values within normal biological range. Our findings could not associate any severe systemic disease, malnutrition, or systemic inflammation with the TMD. Results from our study suggest that serum analyses should neither be used as a biomarker of TMD nor a diagnostic tool for an individual subject with TMD.